Damage mechanism and experimental study of continuous bridges equipped with Sc-FSB. (January 2023) - Zhang, Wenxue; Zheng, Yongrui; Chen, Ying; Su, Lijun; Fang, Rong; Wang, ZhiBin
Abstract: To improve the aseismic performance of continuous bridges, control the residual deformation of the girder and the damage of their fixed piers under strong earthquakes, we propose a new design idea: a continuous bridge equipped with self-centering function-separated bearing (Sc-FSB) located between the fixed pier and the girder. The Sc-FSB would be composed of a sliding bearing (for supporting vertical loads), a friction rope (for bearing horizontal seismic forces and dissipate the seismic energy input to the superstructure), and a spring (for ensuring its self-centering capability). A shaking table test based on a three-span continuous bridge (scale 1:30) and a finite element model analysis were conducted to study the aseismic effect of the Sc-FSB. The shaking table test results showed that the Sc-FSB can significantly reduce the internal force of the fixed pier and the acceleration response of the girder, as well as control the residual displacement of the girder. The spring stiffness and the friction coefficient of the Sc-FSB had a great influence on the seismic performance of the continuous bridge. If reasonable friction coefficients ( μ ) and spring stiffnesses ( K ) are selected, the above Sc-FSB can effectively control the residual displacement of the girder, leading to a good reduction of the fixed pier internal force response and of the displacement response of the girder to seismic events.